Domestic Violence, Employment, and Divorce - Audra Bowlus
Conventional wisdom suggests abused women get caught in a ‘cycle of violence’ and are unable or unwilling to leave their spouses. We estimate a model of domestic violence to determine who abuses, who is abused, and how women respond to abuse via employment and divorce. In contrast to conventional wisdom, abused women are 1.7 to 5.7 times more likely to divorce. Employment before abuse occurs is found to be a significant deterrent. For men, witnessing violence as a child is a strong predictor of abusive behavior: re-socializing men from violent homes lowers abuse rates by 26 to 48 percent.Domestic violence, divorce, marriage, employment